Pemahaman dan Kepatuhan Wajib Pajak terhadap PPN dan PPh Pasal 21 di Jawa Barat - Faridz Maulana Arif; Fauzan Ali Nursya’bani; Muhammad Afif; Muhammad Ikhsan Al Anshori; Rakha Al Gifhari Budiman; Rakha Ariyadi Pratama (Journal of Law and Economics, 2026)
This study examined the understanding and compliance of taxpayers with respect to Value Added Tax (VAT) and Income Tax (PPh) Article 21 in West Java Province. Tax revenue constitutes the primary fiscal base of the Indonesian state, and the country's self-assessment system places the full burden of calculation, payment, and reporting on the taxpayer — making their level of understanding a direct determinant of compliance outcomes. A quantitative survey method was employed, with data gathered through structured questionnaires distributed to individual and corporate taxpayers subject to VAT and/or PPh Article 21 obligations. The findings indicate that taxpayer understanding of VAT and PPh Article 21 regulations does not produce a positive effect on compliance levels, whether measured through reporting behavior or payment conduct. Although overall compliance was relatively adequate, gaps in technical knowledge — particularly in tax administration procedures — remained apparent. Sustained investment in tax education and public outreach is therefore necessary to build more durable compliance patterns across West Java.